BioHiMAG: Biofriendly & High Potential Magnesium Sacrificial Anode - Rathinee, Balakumar; Pook, Ying Nam; Mohd Shahril, A. Rahman; Leela Ambigai, Rajandran; Mohamad Johari, Abu; Ammar Zufar, Abdul Hamid (Universiti Malaysia Perlis (UniMAP), 2010)
Student Affairs & Alumni Department, Universiti Malaysia Perlis had successfully organized ENVEX 2010 (Engineering Invention and Innovation Exhibition 2010) with collaboration of Ministry of Higher Education (MOHE) and Ministry of Science, Technology and Innovation (MOSTI). ENVEX 2010 was held from 2nd - 4th April 2010 at SRJK(C) Khoon Aik Hall, Kangar.